Quantitative Determination of Ascorbic Acid Content in Two Varieties of Bird’s Eye Chili (Capsicum frutescens L.) using UV-Vis Spectrophotometry - Howan, Dian; Saiya, Abdon; Pongoh, Emma (Jurnal Kimia Fullerene, 2025)
This study quantified and compared the ascorbic acid content in green and red bird's eye chili (Capsicum frutescens) using UV-Vis spectrophotometry. The method was optimized by determining the maximum wavelength of ascorbic acid in an acid-stabilized solution, found to be 231 nm. A calibration curve was constructed with standard solutions (25-100 ppm), yielding a linear equation y = 0.0514x + 0.6032 (R² = 0.9361). Sample extracts were prepared and analysed in triplicate at this wavelength. The results demonstrated a significant difference in ascorbic acid concentration between the two varieties. The red chili exhibited a higher concentration of 34.39 ppm in the measured solution, corresponding to 0.90% (b/b) of the fresh weight. In contrast, the green chili contained 23.95 ppm (0.60% b/b). This indicates a 50% higher ascorbic acid content in the mature red fruit. The study concludes that ripening significantly enhances the vitamin C content in bird's eye chili, and the red variety is a nutritionally superior source. The validated method proved effective for the quantitative analysis of ascorbic acid in complex food matrices.